The Importance of Breast Milk From The Science Aspect: Analysis According To The Islamic Perspectives (Keistimewaan Penyusuan Susu Ibu Menurut Sains:Analisis menurut perspektif Islam) - Normadiah, Daud; Mohd A' Tarahim, Mohd Razali; Nadhirah, Nordin; Zurita, Mohd.Yusoff (2018)
Lack of research that analyzes the importance of breastfeeding from science perspective while simultaneously analyzing its importance from the Islamic perspectives is the main issue that drives this research. Based on this matter, the main objective of this research is to study the importance of breastfeeding for both child and mother and analyze it according to the perspectives of Islam. This research is based on literature review method. Data was collected through documents analysis which consists of turath (traditional) and modern books as well as articles related to breastfeeding. It is anticipated that the outcome of this research will be able to explain that the encouragement for breastfeeding is not only due to its significance according to science but also because it fulfils the syarak requirements.